Weakly Compatible Maps Using E.A. and (CLR) Properties in Complex Valued G-Metric Spaces. (30th October 2013) - Singh, Balbir; Gupta, Vishal; Kumar, Sanjay
Abstract : We introduce the notion of complex valuedG -metric spaces and prove common fixed point theorems for weakly compatible maps along with E.A. and (CLR) properties in complex valuedG -metric spaces.